A A bibliometric approach to measuring societal impact of research in biomedicine based on the principle of productive interaction - Grubišić, Marina; Špiranec, Sonja (Qualitative and Quantitative Methods in Libraries; Vol 9 No 2 (2020): June 2020 Issue, 2020)
This paper presents the evolvement of a hybrid framework for the analysis of societal impact of research, based on combining the theory of productive interactions with bibliometric data. This paper presents the next step in the development of the hybrid framework, after we have analyzed the social impact of scientific results as recognized in expert evaluation reports, in the second phase, presented in this paper, we have linked this data with bibliographic data obtained by harvesting the public bibliographic database Croatian scientific bibliography (CROSBI). This second phase of research presents the societally relevant output from public research institutions and faculties on public universities in Croatia in the field of biomedicine for the period from 2013 to 2017. The study has found evidence of measuring societal impact of scientific work using the theory of productive interactions on bibliometrics data in the biomedicine field, thereby contributing to the development of more robust understandings of measuring societal impact in science.